Inclusive educational environment for children with autism in Malaysia primary schools: addressing the issue of way finding - Rahaman, Farjana; Abdul Rahim, Asiah; Abdullah, Fadzidah (IIUM Press, International Islamic University Malaysia, 2018)
Inclusion of children with autism in the mainstream school falls under a regulation in Malaysia. However, existing school buildings still lack in providing enabling environment for children with autism. Moreover, current building standards and policies fail to address the wayfinding design requirements of these children in mainstream educational settings. The present research implies that wayfinding performance of children with autism can be improved by providing an appropriate environment design. This research employs both qualitative and quantitative research methods based on environment and behavior studies. Objectives of this study are (1) to identify different architectural elements that impact on the wayfinding of children with autism and able bodied children, (2) to investigate the existing condition of the primary school buildings in Malaysia in terms of inclusive wayfinding design and finally (3) to suggest a model as a set of tools for design practice that would ensure an appropriate and inclusive learning environment for children with autism, in the context of Malaysia. This research is conducted in five stages. First, through a rigorous literature review on autism and architecture for autism, five design aspects for an enabling environment for autism are identified. At the second stage, based on existing knowledge on wayfinding and school design, twenty wayfinding design parameters are developed that are directly related to these design aspects for an enabling environment for autism. In the third stage, three evaluation tools; Wayfinding Design Parameter Rating Scale (WDPRS), Environmental Assessment (EA) and Performance measure for Children (PMC) are developed and methodology is designed. In the fourth stage, previously identified twenty wayfinding design parameters are further evaluated by the teachers and experts for their relevance using WDPRS. Then an empirical study is carried out in both special and inclusive schools to investigate the performance of children (PMC) in the presence of the twenty wayfinding design parameters as environmental assessment (EA). Finally, based on the findings, design model with a set off tools for wayfinding in inclusive educational spaces is developed to aid the architects and designers